Métodos de extração da areia - SILVA, Theophilo Augusto da (2019)
Searching for shelter, comfort and quality of life, mankind began to explore natural resources. First me used wood, then, the raise of new ways of life, mankind turned to use masonry using minerals that seemed to be inexhaustible. Whit new technologies, industrialization and ways of life, as well as the constructing of new urban centers, the demand of resources, mainly the ones of “in natura” uses on civil construction, like sand, for example, became very large, turning the mineral exploration a predatory activity. The increase of de demand of sand, the expansion of de mining sector and the technology improve, it was observed an increase, of mining enterprise and affected areas although, despite of the competent public organ efforts and related authorities, the technology and concerning with impacted areas, didn’t enhanced in the same way. The Vale do Paraíba do Sul region, São Paulo State, there are many sand ports, and just a few of them recover the affected areas in proper way. This region is the main sand provider to the metropolitan region of the São Paulo and it is the purpose of this work. This work presents the sand extraction methods, the recover after the mining installation, the quell measures, and considerations of the accomplishment of a equilibrated process, the improve the mankind needs, minimizing the environmental impacts.